High-frequency manganese zinc ferrite sintering process and prepared product thereof

Through the high-temperature pre-sintering and solvent surface activation processes, the problems of low density and high power loss caused by the high sintering temperature of manganese zinc ferrite in the existing methods are solved, and densified sintering below 1000°C is achieved, which improves magnetic properties and reduces losses.

CN119735434AActive Publication Date: 2025-04-01SHANDONG CHUNGUANG MAGNETOELECTRIC TECHNOLOGY CO LTD +1

Patent Information

Application Number
CN202411683287.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-04-01
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The temperature of sintering manganese-zeb ferrite in the existing method is generally higher than 1000°C, resulting in low density, poor dimensional consistency, high power loss, and complex process.

Method used

Using high-temperature pre-sintering and solvent surface activation, powder with a particle size of 2 to 5 μm was obtained by ball milling and sieving, and surface activation was carried out by combining water, polyvinyl alcohol and activated solvent with activating agent to achieve sintering below 1000°C.

Benefits of technology

Densified sintering of manganese-zeb ferrite is achieved, and the grain size of 2 to 5 μm is maintained, density and magnetic properties are improved, power loss is reduced, and process operation is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735434A_ABST
    Figure CN119735434A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electronic information materials, in particular to a high-frequency manganese zinc ferrite sintering process and a product prepared through the high-frequency manganese zinc ferrite sintering process. The process comprises the following steps: ball-milling and uniformly mixing main component raw materials and auxiliary component raw materials, pre-sintering at high temperature to obtain pre-sintered powder, grinding, refining and screening the pre-sintered powder, fully mixing the screened powder with an activator solution, kneading and granulating to obtain granules, and pressing and molding the granules to obtain a blank product. And finally, the blank product is subjected to low-temperature sintering at the temperature of 1000 DEG C or below. According to the high-frequency manganese zinc ferrite sintering process, a solvent surface activation method is adopted to improve the sintering activity of thicker (2-5 [mu] m) ferrite pre-sintered powder and reduce the sintering temperature of the ferrite pre-sintered powder, a fine and dense microstructure with uniform crystals can be realized at the sintering temperature of below 1000 DEG C, and finally, the working frequency of above 5MHz is obtained, the density is higher, the magnetic performance is excellent, and the high-frequency manganese zinc ferrite can be obtained. And the high-frequency manganese-zinc ferrite is relatively low in power loss under high frequency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electronic information materials, and in particular to a high-frequency manganese-zinc ferrite sintering process and a prepared product thereof. Background Art

[0002] Manganese-zinc ferrite is mainly used to prepare various inductors, transformers, filters and chokes. It is an important component material and is widely used in electronic communications, national defense and security, etc. Manganese-zinc ferrite is made of iron oxide, zinc oxide, manganese oxide and other oxides through high-temperature solid-phase sintering. Because its resistivity is several orders of magnitude higher than other soft magnetic materials, it can effectively suppress the generation of high-frequency eddy currents, making the operating frequency of ferrite much higher than that of metal-based soft magnetic materials.

[0003] With the large-scale commercial use of 5G communication technology and third-generation semiconductors, the operating frequency of power devices has been increased to MHz, and the requirements for the miniaturization and high-frequency development of corresponding electronic devices are becoming more and more stringent, which requires manganese-zinc ferrite to have a higher operating frequency and lower power loss. When the ferrite grain size is smaller than a certain size, the entire crystal becomes a single domain, and this size is called the critical size of the single domain. By reducing the grain size of the ferrite to a single domain state (≤5μm), the high-frequency domain wall resonance of the manganese-zinc ferrite can be effectively eliminated, thereby increasing the operating frequency and reducing the loss.

[0004] Traditional processes such as solid oxide sintering technology mainly reduce the grain size of manganese zinc ferrite by doping with grain growth inhibitors, but adding too much growth inhibitor will reduce the sintering density, thereby reducing the magnetic permeability and saturation magnetic induction intensity. In addition, lowering the sintering temperature can also reduce the grain size of manganese zinc ferrite. For example, Chinese patents CN107352991B and CN101266859A use coprecipitation and sol-gel methods to prepare manganese zinc ferrite, respectively, and perform low-temperature sintering below 1000°C. However, during the preparation process of the sol-gel method, organic solvents are required to dissolve metal salts, which will result in a certain amount of organic solvent remaining in the final sample, and other unnecessary steps are required to remove it; while the MnZn ferrite particles obtained by the coprecipitation method have the problem of difficult control of grain size and size distribution.

[0005] At present, the commonly used method to reduce the grain size of manganese-zinc ferrite is to use pre-sintered powder ≤ 0.5μm to increase the sintering activity by increasing the powder surface area, but its sintering temperature is generally still higher than 1000℃. Excessively high sintering temperature will lead to abnormal grain growth, uneven grain size, high porosity, high energy consumption and other problems, thereby deteriorating the high-frequency magnetic properties of the material. Therefore, it is of great practical significance to develop a new preparation method for manganese-zinc ferrite so that it can achieve densification sintering below 1000℃ and obtain a fine-grained structure. Summary of the invention

[0006] Technical issues

[0007] The temperature of sintering manganese-zinc ferrite by the existing method is generally still higher than 1000°C, which cannot guarantee the sintering quality of high-frequency and low-power manganese-zinc ferrite materials. The prepared manganese-zinc ferrite has low density and poor dimensional consistency; the manganese-zinc ferrite prepared by the existing method has excessive power loss at high frequency; and the existing method has cumbersome process and complicated operation. The purpose of the present invention is to provide a process for sintering high-frequency manganese-zinc ferrite at low temperature, which is simple to operate, and the prepared manganese-zinc ferrite has not only uniform composition, dense structure, excellent magnetic properties, but also low loss and energy saving.

[0008] Technical Solution

[0009] The first aspect of the present application provides a high-frequency manganese-zinc ferrite sintering process, characterized in that the process comprises the following specific steps:

[0010] a. Weigh the raw material of high-frequency manganese-zinc ferrite, ball-mill the raw material for 5 to 10 hours to mix evenly, and obtain a powder; wherein the raw material is composed of a main component and a secondary component with a content of 0.19 to 0.75wt%; wherein the main component is Fe2O 3、 ZnO and MnO2, the auxiliary component is SnO 2、 Co3O 4、 Composition of In2O3 and TiO2;

[0011] b. The powder is placed in an atmosphere sintering furnace for pre-firing, pre-firing is carried out under an inert atmosphere, the pre-firing temperature is 1100 to 1300 ° C, the temperature is raised to the pre-firing temperature and then kept warm, and after the pre-firing is completed, the pre-firing powder is cooled and discharged from the furnace;

[0012] c. Grind the pre-sintered powder and sieve out powder with a particle size of 2 to 5 μm;

[0013] d. The powder and the activation solvent are fully stirred, kneaded and granulated to obtain a granular material; wherein the activation solvent is composed of water, polyvinyl alcohol and an activator; wherein the activator is one or more of ammonium nitrate, ammonium carbonate or ammonium bicarbonate;

[0014] e. Pressing the above-mentioned granular material into a shape to obtain a rough product;

[0015] f. Place the above-mentioned blank product into an atmosphere sintering furnace for sintering. Sintering is performed under an inert atmosphere at a sintering temperature of 850 to 1000°C. The temperature is raised to the sintering temperature and then maintained. After sintering, the product is cooled and taken out of the furnace to obtain high-frequency manganese-zinc ferrite.

[0016] In some embodiments, based on 100% of the total mass of the main components, the Fe2O3 content is 68-72wt%, the ZnO content is 5.5-9wt%, and the MnO2 content is 19-25wt%; based on 100% of the total mass of the high-frequency manganese-zinc ferrite raw material, the SnO2 content is 0.05-0.25wt%, the Co3O4 content is 0.04-0.15wt%, the In2O3 content is 0.05-0.2wt%, and the TiO2 content is 0.05-0.15wt%.

[0017] In some embodiments, based on 100% of the total mass of the activation solvent, the content of the polyvinyl alcohol is 3-10 wt %, and the content of the activator is 1 wt %-5 wt %.

[0018] In some embodiments, the activator is ammonium nitrate or ammonium carbonate.

[0019] In some embodiments, the constant temperature rise rate in step b is 200-300° C. / h, and the insulation time is 2-3 h.

[0020] In some embodiments, the inert atmosphere in step b and step f maintains a balanced oxygen partial pressure and makes the oxygen partial pressure less than 2%; wherein the inert atmosphere is one of a nitrogen atmosphere, an argon atmosphere or a helium atmosphere.

[0021] In some embodiments, the grinding in step c is performed by mechanical crushing and air flow milling, and the screening is performed by air flow classification.

[0022] In some embodiments, the density of the blank product in step e is 3.0-3.8 g cm -3 .

[0023] In some embodiments, the constant temperature rise rate in step f is 1-10° C. / min, and the insulation time is 4-10 h.

[0024] The second aspect of the present invention provides high-frequency manganese-zinc ferrite prepared by the high-frequency manganese-zinc ferrite sintering process described in any one of the above.

[0025] In some embodiments, the high-frequency manganese-zinc ferrite has a grain size of 2 to 5 μm, a density of ≥95%, a cutoff frequency of ≥5 MHz, and an initial magnetic permeability of higher than 600N.

[0026] Technical Effects

[0027] The ferrite prepared by the traditional method has the problems of abnormal grain growth and poor density. The present invention can improve the crystallinity and spinel phase purity of the pre-sintered powder by high-temperature pre-sintering. After the powder with a particle size of 2 to 5 μm is screened out and activated by the solvent surface, the powder has sufficient sintering activity even if the specific surface area is small, and can be sintered and densified at a temperature below 1000°C. At the same time, the final product grain size is still maintained at 2 to 5 μm, avoiding abnormal growth of grains, effectively maintaining the single domain structure, thereby ensuring its high cutoff frequency. More importantly, the present invention uses a solvent surface activation method to improve the sintering activity of the coarser (2 to 5 μm) ferrite pre-sintered powder and reduce its sintering temperature, and can achieve a uniform fine-grained and densified microstructure at a sintering temperature below 1000°C, and finally obtain a high-frequency manganese-zinc ferrite with an operating frequency of more than 5MHz, a high density and excellent magnetic properties. In addition, the conventional manganese-zinc ferrite has low loss in the high frequency range (500kHz~3M), and the high frequency manganese-zinc ferrite of the present invention has a volume power consumption of no more than 2000kW / m at room temperature, cut-off frequency f=5MHz, B=30mT. 3 . BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Shown is a scanning electron microscope image of the high frequency manganese zinc ferrite prepared in Example 1;

[0029] Figure 2 Shown is a scanning electron microscope image of the high-frequency manganese-zinc ferrite prepared in Comparative Example 1. DETAILED DESCRIPTION

[0030] To facilitate the technical solution of the application, the following first provides a general description and definition of the terms and expressions involved in the application.

[0031] The terms "comprises", "includes" or any other variation thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a list of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus. In the absence of more restrictions, an element defined by the phrase "comprises a ..." does not exclude the presence of additional identical elements in the process, method, article or apparatus that includes the element.

[0032] The term "density" refers to density. For MnZn ferrite, although density is its physical property, it also has a certain influence on its magnetic properties. Increasing density can improve its saturation magnetic induction intensity to a certain extent. In addition, the size of density can reflect the porosity of the microstructure of MnZn ferrite and the uniformity of the organizational morphology to a certain extent. Therefore, increasing density can improve the performance of the material to a certain extent.

[0033] The term "initial permeability" refers to the limit value of the core amplitude permeability when the magnetic field intensity approaches 0. High initial permeability means that the material responds faster to the external magnetic field and can better absorb and conduct magnetic field energy. Therefore, MnZn ferrites with high initial permeability are also widely used in electromagnetic interference and electromagnetic compatibility, and are used to manufacture inductors, transformers, magnetic isolators, etc.

[0034] The term "cut-off frequency" is used to describe a special frequency of the frequency characteristic index. When the cut-off frequency of the material is reached during the application process, the material loss will increase sharply, and the loss will be converted into heat energy and generate heat, affecting the life of the device.

[0035] The "loss" of MnZn ferrite includes three parts: hysteresis loss, eddy current loss and residual loss. In high-frequency applications, residual loss and eddy current loss play a major role.

[0036] The term "activating solvent" in the present invention refers to a mixed solution of activator, water and polyvinyl alcohol.

[0037] The term "solvent surface activation" in the present invention refers to using a certain activation solvent to react with the ferrite powder on the surface, thereby improving the sintering activity of the ferrite powder.

[0038] In each group of comparative experiments provided in this application, unless otherwise specified, except for the differences indicated in each group, other experimental conditions, materials, etc. are kept consistent to ensure comparability.

[0039] Unless otherwise specified, the reagents and instruments used in the embodiments of the present invention can be purchased from the market.

[0040] The following is a further description of a high-frequency manganese-zinc ferrite sintering process and its preparation product provided in this application.

[0041] Example 1: Preparation of high frequency manganese zinc ferrite

[0042] The content of the selected main component raw materials is calculated based on the total mass of the main components as 100%: 70wt% Fe2O3, 5.5wt% ZnO, 24.5wt% MnO2, and the content of the auxiliary component raw materials is calculated based on the total mass of the high-frequency manganese-zinc ferrite raw materials as 100%: 0.05wt% SnO2, 0.04wt% Co3O4, 0.05wt% In2O3, 0.05wt% TiO2. The above main components and auxiliary components are weighed in proportion and put into a ball mill, ball milled for 5 hours to mix evenly, and then the prepared powder is heated to 1100℃ at a speed of 200℃ / h in a nitrogen atmosphere, kept warm for 3 hours, and cooled with the furnace. The high-temperature pre-sintered powder is mechanically crushed and airflow milled, and then an airflow classifier is used to screen out powder with a particle size of 2 to 5μm. The sieved powder is fully stirred, kneaded and granulated with the activation solvent; the activation solvent is composed of water, polyvinyl alcohol and an activator; the polyvinyl alcohol content is 5wt%, the activator content is 1wt%, and the activator is ammonium nitrate. The granulated granules are pressed into a blank product, and the density of the blank product is 3.0g cm -3 The blank product was placed in an atmosphere sintering furnace at a sintering temperature of 850°C for 10 hours. During the sintering process, nitrogen was introduced to make the oxygen partial pressure less than 2%. After cooling out of the furnace, a low-temperature sintered high-frequency manganese-zinc ferrite (Ferrite-1) was obtained. The electron microscope image of the high-frequency manganese-zinc ferrite is shown in FIG. Figure 1 shown.

[0043] Example 2: Preparation of high frequency manganese-zinc ferrite

[0044] The content of the selected main component raw materials is calculated based on the total mass of the main components as 100%: 68wt% Fe2O3, 7wt% ZnO, 25wt% MnO2, and the content of the auxiliary component raw materials is calculated based on the total mass of the high-frequency manganese-zinc ferrite raw materials as 100%: 0.01wt% SnO2, 0.08wt% Co3O4, 0.1wt% In2O3, 0.1wt% TiO2. The above main components and auxiliary components are weighed in proportion and put into a ball mill, ball milled for 10 hours to mix evenly, and then the prepared powder is heated to 1200℃ at a speed of 250℃ / h in a nitrogen atmosphere, kept warm for 3 hours, and cooled with the furnace. The high-temperature pre-sintered powder is mechanically crushed and air flow milled, and then an air flow classifier is used to screen out powder with a particle size of 2 to 5μm. The sieved powder is fully stirred, kneaded and granulated with the activation solvent, wherein the activation solvent is composed of water, polyvinyl alcohol and an activator, wherein the concentration of polyvinyl alcohol is 6wt%, the concentration of the activator is 2wt%, and the activator is ammonium carbonate. The granulated granules are pressed into a blank product, and the density of the blank product is 3.5g cm -3 The rough product was placed in an atmosphere sintering furnace at a sintering temperature of 900°C for 8 hours. During the sintering process, nitrogen was introduced to make the oxygen partial pressure less than 2%. After cooling out of the furnace, low-temperature sintered high-frequency manganese-zinc ferrite (Ferrite-2) was obtained.

[0045] Example 3: Preparation of high frequency manganese zinc ferrite

[0046] The content of the selected main component raw materials is calculated based on the total mass of the main components as 100%: 71wt% Fe2O3, 8wt% ZnO, 21wt% MnO2, and the content of the auxiliary component raw materials is calculated based on the total mass of the high-frequency manganese-zinc ferrite raw materials as 100%: 0.15wt% SnO2, 0.12wt% Co3O4, 0.15wt% In2O3, 0.15wt% TiO2. The above main components and auxiliary components are weighed in proportion and put into a ball mill, ball milled for 8 hours to mix evenly, and then the prepared powder is heated to 1300℃ at a speed of 250℃ / h in a nitrogen atmosphere, kept warm for 2 hours, and cooled with the furnace. The high-temperature pre-sintered powder is mechanically crushed and airflow milled, and then an airflow classifier is used to screen out powder with a particle size of 2 to 5μm. The sieved powder is fully stirred, kneaded and granulated with the activation solvent, wherein the activation solvent is composed of water, polyvinyl alcohol and an activator, wherein the concentration of polyvinyl alcohol is 8wt%, the concentration of the activator is 3wt%, and the activator is ammonium bicarbonate. The granulated material is pressed into a blank product, and the density of the blank product is 3.8g cm -3 The rough product was placed in an atmosphere sintering furnace at a sintering temperature of 950°C for 6 hours. During the sintering process, nitrogen was introduced to make the oxygen partial pressure less than 2%. The product was cooled and taken out of the furnace to obtain low-temperature sintered high-frequency manganese-zinc ferrite (Ferrite-3).

[0047] Example 4: Preparation of high frequency manganese-zinc ferrite

[0048] The content of the selected main component raw materials is calculated based on the total mass of the main components as 100%: 72wt% Fe2O3, 9wt% ZnO, 19wt% MnO2, and the content of the auxiliary component raw materials is calculated based on the total mass of the high-frequency manganese-zinc ferrite raw materials as 100%: 0.25wt% SnO2, 0.15wt% Co3O4, 0.2000wt% In2O3, 0.1wt% TiO2. The above main components and auxiliary components are weighed in proportion and put into a ball mill, ball milled for 10 hours to mix evenly, and then the prepared powder is heated to 1250℃ at a speed of 250℃ / h in a nitrogen atmosphere, kept warm for 3 hours, and cooled with the furnace. The high-temperature pre-sintered powder is mechanically crushed and airflow milled, and then an airflow classifier is used to screen out powder with a particle size of 2 to 5μm. The sieved powder is fully stirred, kneaded and granulated with the activation solvent, wherein the activation solvent is composed of water, polyvinyl alcohol and an activator, wherein the concentration of polyvinyl alcohol is 10wt%, the concentration of the activator is 5wt%, and the activator is ammonium bicarbonate. The granulated material is pressed into a blank product, and the density of the blank product is 3.5g cm -3The blank was placed in an atmosphere sintering furnace at a sintering temperature of 980°C for 8 hours. During the sintering process, nitrogen was introduced to make the oxygen partial pressure less than 2%. The blank was cooled and taken out of the furnace to obtain low-temperature sintered high-frequency manganese-zinc ferrite (Ferrite-4).

[0049] Example 5: Preparation of Comparative High Frequency Manganese-Zn Ferrite

[0050] Comparative Example 1:

[0051] The content of the selected main component raw materials is calculated based on the total mass of the main components as 100%: 70wt% Fe2O3, 5.5wt% ZnO, 24.5wt% MnO2, and the content of the auxiliary component raw materials is calculated based on the total mass of the high-frequency manganese-zinc ferrite raw materials as 100%: 0.05wt% SnO2, 0.04wt% Co3O4, 0.05wt% In2O3, 0.05wt% TiO2. The above main components and auxiliary components are weighed in proportion and put into a ball mill, ball milled for 5 hours to mix evenly, and then the prepared powder is heated to 1100℃ at a rate of 200℃ / h in a nitrogen atmosphere, kept warm for 3 hours, and cooled with the furnace. The high-temperature pre-sintered powder is mechanically crushed and airflow milled, and then an airflow classifier is used to screen out powder with a particle size of 2 to 5μm. The screened powder is fully stirred, kneaded and granulated with water and polyvinyl alcohol, wherein the concentration of polyvinyl alcohol is 5wt%. The pellets obtained by granulation are pressed into blank products with a density of 3.0 g cm -3 The blank was placed in an atmosphere sintering furnace at a sintering temperature of 850°C for 10 hours. During the sintering process, nitrogen was introduced to make the oxygen partial pressure less than 2%. After cooling out of the furnace, a low-temperature sintered high-frequency manganese-zinc ferrite (Ferrite-5) was obtained. The electron microscope image of the high-frequency manganese-zinc ferrite is shown in FIG. Figure 2 shown.

[0052] Comparative Example 2:

[0053] The content of the selected main component raw materials is calculated based on the total mass of the main components as 100%: 68wt% Fe2O3, 7wt% ZnO, 25wt% MnO2, and the content of the auxiliary component raw materials is calculated based on the total mass of the high-frequency manganese-zinc ferrite raw materials as 100%: 0.01wt% SnO2, 0.08wt% Co3O4, 0.1wt% In2O3, 0.1wt% TiO2. The above main components and auxiliary components are weighed in proportion and put into a ball mill, ball milled for 10 hours to mix evenly, and then the prepared powder is heated to 1200℃ at a rate of 250℃ / h in a nitrogen atmosphere, kept warm for 3 hours, and cooled with the furnace. The high-temperature pre-sintered powder is mechanically crushed and airflow milled, and then an airflow classifier is used to screen out powder with a particle size of 2 to 5μm. The screened powder is fully stirred, kneaded and granulated with water and polyvinyl alcohol, wherein the concentration of polyvinyl alcohol is 6wt%. The pellets obtained by granulation are pressed into blank products with a density of 3.5 g cm -3The blank was placed in an atmosphere sintering furnace at a sintering temperature of 900°C for 8 hours. During the sintering process, nitrogen was introduced to make the oxygen partial pressure less than 2%. The blank was cooled and taken out of the furnace to obtain low-temperature sintered high-frequency manganese-zinc ferrite (Ferrite-6).

[0054] Example 6: Characterization of high frequency manganese-zinc ferrite

[0055] The high-frequency manganese-zinc ferrite prepared in Examples 1-4 and Comparative Examples 1-2 was characterized as follows:

[0056] (1) Grain size test: The grain size of high frequency manganese zinc ferrite was measured using a scanning electron microscope (model: ZEISS Sigma 300).

[0057] (2) Density test: Use the drainage method to measure the density of high-frequency manganese-zinc ferrite. The theoretical density of general ferrite is 5.5g / cm 3 , actual density / theoretical density = density.

[0058] (3) Cut-off frequency test: The cut-off frequency of high-frequency manganese-zinc ferrite was measured using an impedance analyzer (model: Keysight E4991B).

[0059] (4) Test of initial magnetic permeability: An impedance analyzer (model: Keysight E4991B) was used to measure the magnetic properties of high-frequency manganese-zinc ferrite.

[0060] (5) Loss test: Use BH analyzer (model: Yantong SY8218) to measure the loss of high-frequency manganese-zinc ferrite.

[0061] The characterization results are shown in Table 1.

[0062] Table 1 Characterization results of high frequency manganese zinc ferrite

[0063]

[0064] The results are shown in Table 1. By comparing the high-frequency manganese-zinc ferrite prepared in Example 1 with that prepared in Comparative Example 1, under the same main component, auxiliary component, sintering process and other conditions, Example 1 introduces ammonium nitrate solvent for surface activation. Under the condition of unchanged grain size, the density of Example 1 is significantly improved (68%→96%) compared with Comparative Example 1, which leads to a significant improvement in magnetic permeability (180→620) and a significant reduction in loss (6550kW / m 3 →1950kW / m 3 ).

[0065] Comparing the high-frequency manganese-zinc ferrite prepared in Example 2 with that in Comparative Example 2, when the main components, auxiliary components, sintering processes and other processes are the same, the density of Example 2 has been significantly improved (76%→95%) compared with Comparative Example 2 under the condition that the grain size remains unchanged due to the introduction of ammonium carbonate for solvent surface activation, resulting in a significant improvement in magnetic permeability (143→680) and a significant reduction in loss (5920kW / m 3 →1800kW / m 3 ).

[0066] The above specific implementation methods further illustrate the purpose, technical solutions and beneficial effects of the present application in detail. It should be understood that the above are only specific implementation methods of the present application and are not used to limit the protection scope of the present application. Any modifications, equivalent substitutions, improvements, etc. made on the basis of the technical solutions of the present application should be included in the protection scope of the present application.

Claims

1. A high frequency manganese-zinc ferrite sintering process, characterized in that: The process comprises the following specific steps: a. Weigh the raw materials of high-frequency manganese-zinc ferrite, and mix the raw materials by ball milling to obtain powder; wherein the raw materials are composed of a main component and a secondary component with a content of 0.19 to 0.75wt%; wherein the main component is Fe2O 3、 ZnO and MnO2, the auxiliary component is SnO 2、 Co3O 4、 Composition of In2O3 and TiO2; b. The powder is placed in an atmosphere sintering furnace and pre-fired under an inert atmosphere at a temperature of 1100 to 1300 ° C. The temperature is raised to the pre-fired temperature and then kept warm. After the pre-fired temperature is completed, the pre-fired powder is cooled and discharged from the furnace to obtain the pre-fired powder; c. Grind the pre-sintered powder and sieve out powder with a particle size of 2 to 5 μm; d. The powder and the activation solvent are fully stirred, kneaded and granulated to obtain a granular material; wherein the activation solvent is composed of water, polyvinyl alcohol and an activator; wherein the activator is one or more of ammonium nitrate, ammonium carbonate or ammonium bicarbonate; e. Pressing the above-mentioned granular material into a shape to obtain a rough product; f. Place the above-mentioned blank product into an atmosphere sintering furnace and sinter it under an inert atmosphere at a sintering temperature of 850-1000°C. Rise the temperature to the sintering temperature and then keep it warm. After sintering, cool it down and get out of the furnace to obtain high-frequency manganese-zinc ferrite.

2. The high frequency manganese-zinc ferrite sintering process according to claim 1, characterized in that: Based on 100% of the total mass of the main components, the Fe2O3 content is 68-72wt%, the ZnO content is 5.5-9wt%, and the MnO2 content is 19-25wt%; based on 100% of the total mass of the high-frequency manganese-zinc ferrite raw material, the SnO2 content is 0.05-0.25wt%, the Co3O4 content is 0.04-0.15wt%, the In2O3 content is 0.05-0.2wt%, and the TiO2 content is 0.05-0.15wt%.

3. The high frequency manganese-zinc ferrite sintering process according to claim 1, characterized in that: Based on 100% of the total mass of the activation solvent, the content of the polyvinyl alcohol is 5-10wt%, and the content of the activator is 1-5wt%.

4. The high frequency manganese-zinc ferrite sintering process according to claim 3, characterized in that: The activator is ammonium nitrate or ammonium carbonate.

5. The high frequency manganese-zinc ferrite sintering process according to claim 1, characterized in that: The constant temperature rise rate in step b is 200-300° C. / h, and the insulation time is 2-3 h.

6. The high frequency manganese-zinc ferrite sintering process according to claim 1, characterized in that: The inert atmosphere in step b and step f maintains a balanced oxygen partial pressure and makes the oxygen partial pressure less than 2%; wherein the inert atmosphere is one of a nitrogen atmosphere, an argon atmosphere or a helium atmosphere.

7. The high frequency manganese-zinc ferrite sintering process according to claim 1, characterized in that: The grinding and refining in step c is carried out by mechanical crushing and air flow mill crushing, and the screening is carried out by air flow classification.

8. The high frequency manganese-zinc ferrite sintering process according to claim 1, characterized in that: The density of the blank product in step e is 3.0-3.8 g cm -3 .

9. The high frequency manganese-zinc ferrite sintering process according to claim 1, characterized in that: The constant temperature rise rate in step f is 1-10°C / min, and the insulation time is 4-10h.

10. The high-frequency manganese-zinc ferrite prepared by the high-frequency manganese-zinc ferrite sintering process according to any one of claims 1 to 9, characterized in that: The high-frequency manganese-zinc ferrite has a grain size of 2-5 μm, a density of ≥95%, a cut-off frequency of ≥5 MHz, and an initial magnetic permeability of higher than 600N.

Citation Information

Patent Citations

  • Method for quick sintering of micro-crystal ferrite magnetic core part

    CN101266859A

  • A kind of manganese-zinc / nickel-zinc composite ferrite with core-shell structure and preparation method thereof

    CN107352991B

  • Method for preparing high-dielectric active microwave medium ceramic material

    CN108911708A

  • A preparation method of soft magnetic ferrite material

    CN109192434A

  • Magnetic material particles, dust core and coil component

    CN110178190A

Cited By

  • Manganese zinc ferrite material as well as preparation method and application thereof

    CN120117886A